Estimation of transient boundary heat flux by using hybrid algorithm in a two dimensional laminar duct flow - Thakkar, V; Prajapati, R; Shah, S; Parwani, A K (Journal of physics. Conference series, 2021)
Conjugate gradient method (CGM) with adjoint problem is a popular optimization algorithm in solving the inverse heat transfer problems. It starts with the initial guess solution of unknown parameters to be estimated which would be updated in an iterative procedure. The initial guess solution is one of the significant factors for the accuracy of estimation. In the current study, the Jaya algorithm has been developed to provide the initial guess solution to CGM. The resultant algorithm is called hybrid algorithm. The test problem considered here for the study is the estimation of transient boundary heat flux for two-dimensional hydrodynamically developed and thermally developing forced convective laminar duct flow. The hybrid algorithm is found to be robust and accurate than CGM.